2023
DOI: 10.1002/pen.26278
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of polylactic acid/natural fiber extruded composites

Abstract: In this work, the fabricated polylactic acid (PLA) and hybrid natural fiber (NF) biocomposites via a melt extrusion method were investigated. NFs from locally grown plants were utilized as fillers. Polyethene glycol (PEG) was used as the plasticizer to improve the processability of the PLA. The effect of PLA/NF biocomposite processing was assessed by mechanical characterization (tensile, modulus, strain at break, and impact tests), and thermal properties (thermogravimetric analysis and differential scanning ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…2b and d). 36,37 Therefore, we focused on the PLGA/PLLA nanofibrous composite membranes in this study.…”
Section: Resultsmentioning
confidence: 99%
“…2b and d). 36,37 Therefore, we focused on the PLGA/PLLA nanofibrous composite membranes in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, natural fiber is a sustainable resource that is inexpensive, nontoxic, lightweight, and biodegradable 22,23 . It also improved the mechanical properties of the polymer matrix 23,24 . OPF as agricultural waste, which has high toughness and contains a large amount of cellulose, 25 can be used to enhance the properties of the polymer matrix 23,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…22,23 It also improved the mechanical properties of the polymer matrix. 23,24 OPF as agricultural waste, which has high toughness and contains a large amount of cellulose, 25 can be used to enhance the properties of the polymer matrix. 23,25,26 Jawaid et al 23 found that the addition of OPF led to improve the impact strength of polymer composites.…”
mentioning
confidence: 99%
“…The properties of fabric‐based composites are contingent upon several factors, including the kind and origin of the fibers, fiber content, and the polymeric matrix 5,20,21 . Among the polymer matrices, PLA stands out as the favored due to its biodegradability and its derivation from renewable sources, 22,23 which has garnered significant interest from the scientific community 24 . Moreover, a number of scholars have demonstrated an acute attention in PLA and its composites as a viable alternative to petroleum‐derived products 25–28 …”
Section: Introductionmentioning
confidence: 99%